2017
DOI: 10.1186/s13028-017-0322-z
|View full text |Cite
|
Sign up to set email alerts
|

Questionnaire survey of detrimental fur animal epidemic necrotic pyoderma in Finland

Abstract: BackgroundIn 2007, a previously unrecorded disease, fur animal epidemic necrotic pyoderma (FENP), was detected in farmed mink (Neovision vision), foxes (Vulpes lagopus) and Finnraccoons (Nyctereutes procyonoides) in Finland. Symptoms included severe pyoderma with increased mortality, causing both animal welfare problems and economic losses. In 2011, an epidemiologic questionnaire was mailed to all members of the Finnish Fur Breeders’ Association to assess the occurrence of FENP from 2009 through the first 6 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…For the Palomino/ Pearl beige and Brown mink this number were 0.54 and 0.04 respectively. This could indicate that Brown mink may be more resistant towards FNP compared to the other colour types; an observation also presented by Nordgren et al [6]. The above mentioned difference may have been affected by the fact that this study was conducted on different farms with potentially different strategies, methods and different feed kitchens.…”
Section: Table 2 Results From Farm A-c Compared To National Averagementioning
confidence: 67%
See 2 more Smart Citations
“…For the Palomino/ Pearl beige and Brown mink this number were 0.54 and 0.04 respectively. This could indicate that Brown mink may be more resistant towards FNP compared to the other colour types; an observation also presented by Nordgren et al [6]. The above mentioned difference may have been affected by the fact that this study was conducted on different farms with potentially different strategies, methods and different feed kitchens.…”
Section: Table 2 Results From Farm A-c Compared To National Averagementioning
confidence: 67%
“…The mechanisms behind variation in the occurrence of FNP between individuals and farms remain unknown. Suggested factors include genetics, immunological robustness and transfer of mink [6,9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Picket and Harris, 2015;Mustonen et al, 2017) Morbidity = (e.g., in mink, foxes, racoon dogs, raccoons, & marmots) numerous bacterial/protozoan/viral/ectoparasite infections, causing conditions including enteric disease, necrotic pyoderma, pneumonia, obesity, leg weakness, negative mobility, abrasions, pressure lesions, skeletal pathology (carpal joint laxity and locomotor deficits), periodontal disease, eye disease, and negative genetic traits and associated conditions. (Kempe et al, 2010;Plotnikov, 2012;Ellick et al, 2013;Picket and Harris, 2015;Brash et al, 2016;Hammer et al, 2016;Kempe and Strandeń, 2016;Moisander-Jylhä et al, 2016;Nordgren et al, 2016a;Nordgren et al, 2016b;Smura et al, 2016;Mustonen et al, 2017;Kempe, 2018;Devaux et al, 2021;Klockiewicz et al, 2021;Linzey and Linzey, 2022) High premature mortality = e.g., 15 -50% mortality to weaning among foxes, 99% mortality among mink kits. (Picket and Harris, 2015;Linzey and Linzey, 2022) Physical mistreatment and abuse = rough treatment of animals during handling and (Picket and Harris, 2015;Arney, 2022;Linzey and Linzey, 2022) (Continued)…”
Section: Issues Referencesmentioning
confidence: 99%
“…Furthermore, widespread populations of the American mink and racoon dog have their origins clearly traced to releases in the Russian Federation from fur farms, where the species were first recorded (Balakirev and Tinaeva, 2001). A study in Denmark on the invasive racoon dog, (Nordgren, 2017) used 4000 SNPs to show that the species originated from Danish fur farm escapes and releases. Genetic studies have shown that often animals from different fur farms have genetically distinct profiles so it is possible to track their spread.…”
Section: Issues Referencesmentioning
confidence: 99%